The Perception of the Church on Corruption: A Case Study of Good Shepherd Africa Gospel Church, Nairobi - Kenya (Impact: Journal of Transformation, 2021)
The subject of corruption in political leadership and the church’s involvement is the most complex in Kenya, it is always emotive to discuss. Corruption has been described as one of the greatest evils of this generation, and the enemy of economic and social development. The purpose of this study was to find out the perception of the church on corruption in political leadership and the church's response to the situation. The researcher sought to find out how Christians perceive and talk about corruption, their position and in which ways they have experienced corruption, whether they feel mandated to speak against it or are intimidated. The researcher used a qualitative methodology with in-depth questionnaires; interviews were conducted for data collection. The study findings revealed that the church is aware of corruption in political leadership, but no evidence showed the church’s efforts in responding to the situation. The Church has to consider her calling and responsibility in challenging the government on the issue of corruption. Failing to do so may raise questions whether the church is also corrupted or not faithful to her mission. The Church as the voice of God in society has the mandate to resist any opposition to development and peace of any society caused by the corruption of whatever forms, speaking on behalf of vulnerable people, especially those who are oppressed without justice. There is a need for the Church to consider discipleship as the key focus to help believers fully understand how to deal with the issue of corruption in their daily lives.